Pengaruh Pendidikan Kewirausahaan Berkelanjutan dan Altruisme dimoderasi Jenis Bidang Studi Terhadap Intensi Berwirausaha Hijau Mahasiswa Universitas Sebelas Maret - Ramadhan, Syahdan Sandhika; Sudarno, Sudarno; Sabandi, Muhammad (Jurnal Pendidikan Ekonomi (JUPE), 2024)
Green entrepreneurship is an interesting subject to discuss in the entrepreneurship sector. However, research related to this field is still limited, so further research needs to be done. This study was conducted to determine the effect of sustainable entrepreneurship education and altruism on green entrepreneurial intentions moderated by the type of field of study. The sample in this study were 380 active students of Sebelas Maret University. The sampling technique in this study used purposive sampling with data collection through questionnaires. The moderating regression analysis method was used as a data analysis technique. The results obtained in this study, namely: 1) There is a positive and significant influence between sustainable entrepreneurship education on green entrepreneurial intention; 2) There is a positive and significant influence between altruism on green entrepreneurial intention; 3) Type of field of study can moderate the relationship between sustainable entrepreneurship education on green entrepreneurial intention; 4) Type of field of study can moderate the relationship between altruism on green entrepreneurial intention.